Effect of Delayed Bonding and Antioxidizing Agent on Shear Bond Strength of Resin Composite to Enamel and Dentin after Tooth Bleaching - Abdulghani I Mira, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The present study aimed to investigate the effect of delayed bonding and antioxidizing agent on shear bond strength of bleached enamel and dentin. Forty extracted premolars were mounted in clear acrylic, ground to expose flat enamel and dentin surfaces, and bleached using 35% carbamide peroxide. Specimens were divided into two groups of 20, each was subdivided into two equal subgroups n = 10. In first and second subgroups, composite resin was applied to both enamel and dentin substrates immediately (T0) and after 7 days (T1) from bleaching respectively. In the third and forth subgroups, bleached substrates were pretreated with 10% sodium ascorbate before T0 and T1 composite application respectively. Shear bond strength was tested and data were statistically analyzed using ANOVA and "student's" t-test at p ? 0.05. A significant increase in the shear bond strength was detected after sodium ascorbate treatment both in enamel and dentin substrates (from 8.57 ± 0.84 to 12 ± 1.97 MPa and from 11.51 ± 1.32 to 15.57 ± 1.55 MPa, respectively) with immediate application of composite resin (p ? 0.05). Statistical significance (p ? 0.05) was also found after delayed application of composite with and without sodium ascorbate in both enamel and dentin. It can be concluded that, Sodium ascorbate treatment for bleached enamel and dentin improved the bond strength, especially after delayed composite application.